2003
DOI: 10.1023/a:1026032404105
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Generation of reactive oxygen species (ROS) is a normal process in the life of aerobic organisms. Under physiological conditions, these deleterious species are mostly removed by the cellular antioxidant systems, which include antioxidant vitamins, protein and non-protein thiols, and antioxidant enzymes. Since the antioxidant reserve capacity in most tissues is rather marginal, strenuous physical exercise characterized by a remarkable increase in oxygen consumption with concomitant production of ROS presents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(107 citation statements)
references
References 25 publications
6
87
0
11
Order By: Relevance
“…Levels of antioxidants are known to vary depending on the intensity, type and length of exercise (23). However, it was reported that the activity of antioxidant enzymes like SOD and catalase in the blood and tissues increased after acute exercise (24). Exercise may be increase the antioxidant defense in general.…”
Section: P Values;mentioning
confidence: 97%
“…Levels of antioxidants are known to vary depending on the intensity, type and length of exercise (23). However, it was reported that the activity of antioxidant enzymes like SOD and catalase in the blood and tissues increased after acute exercise (24). Exercise may be increase the antioxidant defense in general.…”
Section: P Values;mentioning
confidence: 97%
“…34,35,[41][42][43][44] As a non-protein thiol source in mammalian cells, the tripeptide glutathione system has an key role in the maintenance of cellular redox status, and especially important for cellular defense against ROS. 45,46 Glutathione can directly scavenge free radicals in non-enzymatic reactions, and reduce hydrogen peroxide via a reaction catalyzed by the glutathione peroxidases. 46,47 Previous studies have revealed that glutathione deficiency are closely associated with ROS production.…”
Section: Epigeneticsmentioning
confidence: 99%
“…45,46 Glutathione can directly scavenge free radicals in non-enzymatic reactions, and reduce hydrogen peroxide via a reaction catalyzed by the glutathione peroxidases. 46,47 Previous studies have revealed that glutathione deficiency are closely associated with ROS production. 45,48 SOD is one of the main ROS enzymatic scavengers, catalyzing the dismutation of superoxide into H 2 O 2 and O 2 , and having an important role in vascular tone, lung function and metabolism of NO.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Regarding the elevated reactive oxygen species (ROS) and urate generation during physical activity, [9][10][14][15][16] urate recirculation in the PT cells seems quite logical and may have some physiological importance in preventing hazardous effects of ROS and maintaining the integrity of the PT cells. Therefore, reduced urate reabsorption or excretion may deteriorate the maintenance of the normal uric acid homeostasis in exercisers.…”
Section: Introductionmentioning
confidence: 99%